The City of Short-distance Trips and Long-distance Journeys - Holz-Rau, Christian; Holz-Rau, Christian; Sicks, Kathrin (Raumforschung und Raumordnung | Spatial Research and Planning, 2013)
There is a bulk of research on spatial differences in travel behaviour, more specifically travel distances. This research suggests that the distances travelled by the population of small municipalities are longer than that by the population of larger cities. However, related studies focus mainly on daily travel. Long-distance trips are included as a minor aspect ‘on top’, if at all. Often they are deliberately excluded from analysis due to the focus on daily travel. On the other hand, long-distance travel accounts for a large fraction in total mileage due to the length of trips. In this paper we study travel distances in daily trips and long-distance trips, comparing municipality size categories. We also study the sum of annual travel distances on the individual level. We use descriptive statistics as well as Heckman models and OLS regressions, controlling for various sociodemographics. We find distances travelled for long-distance trips and daily trips to be affected by sociodemographics in much the same way, while spatial effects affect distances travelled for daily and long-distance trips in different directions. While daily travel distances are negatively associated with municipality size, it is the other way round for long-distance trips. As an outcome, the travel reduction effect of large cities is largely compensated for by long-distance trips.